PENEGAKAN HUKUM TERHADAP DOKTER YANG MENOLAK PEMBUATAN VISUM ET REPERTUM DALAM TINDAK PIDANA PEMBUNUHAN ( Studi Kalimatan Barat ) - KUSMAYADI, SH. A.2121100, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACT This study discusses the demand for expert assistance in the investigation phase as mentioned in Article 120 paragraph(1) Criminal Procedure Code and the expert testimony Requests for assistance at this stage ofthe proceedings provided for in Article 180 paragraph (1) expert testimony KUHAP. About mentioned in the second chapter of the Criminal Procedure Code in above, given the sense of Article1, point to the 28th criminal Procedure Code, which states that: "information is the expert testimony given by a person who hasspecial expertise about the things needed to make light of a criminal case for the purpose of examination".The background of this research related to expert testimony necessary assistance in the process of acriminal case, then thisaid in the investigation stage also has an important role to help investigators find and collectevidence in an attemptt of in the material truth of a criminal case.Expert testimony is the testimony of a doctor whohad been appo intedo athunder Government Regulation No.26 Year 1960 on Oath Pronunciation doctor, who can help investigators in providing evidence. Intended to doctors are set for thin writingin the form of a medical examination called visum et repertum. The problem is the fact there are some doctors refuse to make Visum et repertum, because they thought no forensic doctor, while the existing law article 186 of the Criminal Procedure Code, 1937 Gazette No.350 states Visum et repertum include in gevidence, a statement made by a doctor put in the form written How analytical formulation of the problem is enforcement against doctors who refuse making visum et repertum in criminal homicide in the perspective of criminal law and legislation? What are the limiting factors in the process of enforcing the law against doctors who refuse making visum et repertum the crime of murder? Method research approach examines normative juridical legal issue with a qualitative approach through normative data collection techniques (literature) and empirical (field research). This study tries to answer the issu esraised in this research by looking at legislation, legal theories, and the national and international legal instruments that exist, then looks traight implementation in the field.Research in the specification of this research is descriptive specifically, in order to describe the existing situation by using scientific research methods. The fact that there is then illustrated with an interpretation, evaluation and general knowledge, because the facts have no meaning without interpretation, evaluation and general knowledge. The results of analysis is that Article 184 paragraph(1), letterc of the Criminal Procedure Code as well as the documentary evidence in Article 187 which states that the letter cletter as referred to in Article 184 paragraph(1) c, made on oathor confirmed by oath, or Letter testimony of an expert opinion based on his expertise about something or something formally requested state from him.Article 53 of the Health ActNo.36 of 2009 subsection(3) states of health workers, one of whom is a doctor. If the doctor refuses, it may be subject to Article 224 of the Criminal Code.In the manufacture of Law Enforcement Visum et repertum by doctors to see how factors, namely: (1) barriers in manufacturing, among others, are away homesand the limited power of judicial physicians who make Visum et repertum,(2) Barriers to implementation is making Visum et repertum some times less complete and manufacture of Visum et repertum not done as soon aspossible(3) The state of decaying corpses. Such circum stances may affect the results of the autopsy. (4) Lack of coordination between the lead investigator doctor Demand procedure Visum et repertumto take a long time.(5) From The Investigators such as delay request Visum et repertum. (6) From the Family Party for not allow an autopsy, (7) From The doctors because they need a place to carry out further investigation (8) For accident victims who live, many victims who refuse to do visum et repertum therefore do not know the benefits and usefulness, (9) lack of un familiarity with laws and regulations, that Visum et repertum a written statement categorized as expert witness testimony and documentary evidence and should be made by doctors.Actuallythere is noreason fora doctor to refuse to make visum et repertum, because the forensic medical science is only a branch of medical science that uses medical knowledge and technology for the benefit of law enforcement and justice. The goal is injuries, poisoning or death for the crime(Article 133 KUHAP).Professional standards in the field of forensic medicine doctor as a minimum standard of knowledge and skills that must be mastered in a doctor use science and medical technology to help law enforcement, justice and solve legal problems. Refusal of doctors to not make the post mortem repertumer actually has no legal base, Article 179(1) Criminal Procedure Code gives the assertion that each person was asked his opinion as an expert medicaldoctor or other judicialor required to provide expert testimony for justice.Based onthis article givest wooptions, namely the judicial medical expertor doctor. Visum et Repertum or VeR is a written statement made by the physician based on the examination of the person or people suspected, based onthe written request of the authorities, and are made keeping in mind the oath of office and the Criminal Code. Visum et repertum role as one of the valid evidence for pro of of criminal cases against human health and life. In ver there is a description of the medical results are contained in the news section, which can therefore be considered as a substitute for evidence. Ver also includes information or opinion about the results of the medical examination the doctor stated in the conclusion section.Keywords: Law Enforcement, Visum et Repertum, Doctors Professional Standards.AbstrakPenelitian ini membahas tentang permintaan bantuan tenaga ahli pada tahap penyidikan sebagaimana disebutkan pada Pasal 120 ayat (1) KUHAP dan Permintaan bantuan keterangan ahli pada tahap pemeriksaan persidangan diatur dalam Pasal 180 ayat (1) KUHAP.Mengenai keterangan ahli sebagaimana disebutkan dalam kedua pasal KUHAP di atas, diberikan pengertiannya pada Pasal 1 butir ke-28 KUHAP, yang menyatakan bahwa: Keterangan ahli adalah keterangan yang diberikan oleh seorang yang memiliki keahlian khusus tentang hal yang diperlukan untuk membuat terang suatu perkara pidana guna kepentingan pemeriksaan.Terkait dengan bantuan keterangan ahli yang diperlukan dalam proses pemeriksaan suatu perkara pidana, maka bantuan ini pada tahap penyidikan juga mempunyai peran yang cukup penting untuk membantu penyidik mencari dan mengumpulkan bukti-bukti dalam usahanya menemukan kebenaran materiil suatu perkara pidana. Keterangan ahli yang dimaksud yaitu keterangan dari dokter yang telah diangkat sumpah berdasarkan Peraturan Pemerintah Nomor 26 Tahun 1960 tentang Lafal Sumpah Dokter, yang dapat membantu penyidik dalam memberikan bukti. Keterangan dokter yang dimaksudkan tersebut dituangkan secara tertulis dalam bentuk surat hasil pemeriksaan medis yang disebut dengan visum et repertum.Permasalahannya adalah dalam kenyataannya ada sebagian dokter menolak untuk membuat Visum et repertum, karena beranggapan bukan dokter forensik, sedangkan perangkat hukum yang ada pasal 186 KUHAP, Staatblad 1937 Nomor 350 menyatakan Visum et repertum termasuk alat bukti, surat keterangan yang dibuat oleh dokter dituangkan dalam bentuk tertulis.Perumusan masalahnya adalah Bagaimana analisis penegakan hukum terhadap dokter yang menolak pembuatan visum et repertum dalam tindak pidana pembunuhan dalam perspektif hukum pidana dan peraturan perundang-undangan ?Apa yang menjadi faktor-faktor penghambat dalam proses penegakan hukum terhadap dokter yang menolak pembuatan visum et repertum dalam tindak pidana pembunuhan ?Hasil penelitian analisisnya adalah bahwa Pasal 184 ayat (1), huruf c KUHAP mengenai alat bukti surat serta pasal 187 huruf c yang menyatakan bahwa surat sebagaimana tersebut pada pasal 184 ayat (1) c, dibuat atas sumpah jabatan atau dikuatkan dengan sumpah, atau Surat keterangan dari seorang ahli yang pendapatnya berdasarkan keahliannya mengenai sesuatu hal atau sesuatu keadaan yang diminta secara resmi dari padanya. Pasal 53 Undang-Undang Kesehatan No 36 Tahun 2009 ayat (3) menyatakan tenaga kesehatan, salah satunya adalah dokter. Apabila dokter menolak, maka dapat dikenakan Pasal 224 KUHP. Dalam Penegakan Hukum pembuatan Visum et repertum oleh dokter menemui berapa faktor, yaitu : (1) Hambatan dalam pembuatan antara lain adalah jauhnya rumah dan terbatasnya tenaga dokter kehakiman yang membuat Visum et repertum, (2)Hambatan dalam penerapan adalah pembuatan Visum et repertum terkadang kurang lengkap dan pembuatan Visum et repertum tidak dilakukan sesegera mungkin (3)Keadaan mayat sudah membusuk. Keadaaan seperti ini dapat mempengaruhi hasil dari visum. (4)Kurang koordinasi antara penyidik dengan dokter yang mengakibatkan prosedur permintaaan Visum et repertum menjadi memakan waktu yang lama. (5) Dari Pihak Penyidik seperti keterlambatan permintaan Visum et repertum. (6)Dari Pihak Keluarga karena tidak mengijinkan dilakukan autopsi, (7) Dari Pihak dokter karena butuh tempat untuk melaksanakan pemeriksaan lanjutan (8)Untuk korban Kecelakaan yang hidup, banyak korban yang menolak untuk dilakukan visum et repertum oleh karena belum mengetahui manfaat dan kegunaannya , (9)Ketidak pahaman terhadap peraturan perundang-undangan,bahwa Visum et repertum sebuah keterangan tertulis yang dikatagorikan sebagai keterangan saksi ahli dan bukti surat dan harus dibuat oleh dokter. Sebenarnya tidak ada alasan dokter untuk menolak membuat visum et repertum, karena ilmu kedokteran forensik adalah hanya suatu cabang ilmu kedokteran yang mempergunakan ilmu pengetahuan dan teknologi kedokteran untuk kepentingan penegakan hukum dan keadilan. Sasarannya adalah korban luka, keracunan atau mati karena tindak pidana (Pasal 133 KUHAP). Standar profesi dokter dibidang kedokteran forensik sebagai standar keilmuan dan ketrampilan minimal yang harus dikuasai seorang dokter dalam menggunakan ilmu pengetahuan dan teknologi kedokteran untuk membantu penegakan hukum, keadilan dan memecahkan masalah-masalah hukum. Penolakan dokter untuk tidak membuat visum er repertum sebenarnya tidak memiliki alas hukum, Pasal 179 (1) KUHAP memberikan penegasan, bahwa Setiap orang diminta pendapatnya sebagai ahli kedokteran kehakiman atau dokter atau lainnya wajib memberikan keterangan ahli demi keadilan. Berdasarkan pasal ini memberikan pilihan dua, yakni ahli kedokteran kehakiman atau dokter. Visum et Repertum atau VER adalah laporan tertulis yang dibuat oleh dokter berdasarkan pemeriksaan terhadap orang atau yang diduga orang, berdasarkan permintaan tertulis dari pihak yang berwenang, dan dibuat dengan mengingat sumpah jabatan dan KUHP. Visum et repertum berperan sebagai salah satu alat bukti yang sah dalam proses pembuktian perkara pidana terhadap kesehatan dan jiwa manusia. Dalam VeR terdapat uraian hasil pemeriksaan medis yang tertuang dalam bagian pemberitaan, yang karenanya dapat dianggap sebagai pengganti barang bukti.VeR juga memuat keterangan atau pendapat dokter mengenai hasil pemeriksaan medis yang tertuang dalam bagian kesimpulan.Kata kunci: Penegakan Hukum, Visum et Repertum, Standar Profesi Dokter.